2020
DOI: 10.5194/bg-17-231-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the North Atlantic deoxygenation by the slowdown of the nutrient stream

Abstract: Abstract. Western boundary currents act as transport pathways for nutrient-rich waters from low to high latitudes (nutrient streams) and are responsible for maintaining midlatitude and high-latitude productivity in the North Atlantic and North Pacific. This study investigates the centennial oxygen (O2) and nutrient changes over the Northern Hemisphere in the context of the projected warming and general weakening of the Atlantic Meridional Overturning Circulation (AMOC) in a subset of Earth system models includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…A10). However, similar to what has been shown for the North Atlantic in coarse resolution ESM projections (Whitt, 2019;Tagklis et al, 2020;Whitt and Jansen, 2020), the decrease in nutrient supply is also controlled by the sub-surface nutrient reservoir and the fluxes fueling it. Nitrate concentrations in the top 400 metres strongly decrease under our global-warming scenario (Fig.…”
Section: Decline In Nutrient Supply Pathwayssupporting
confidence: 72%
See 2 more Smart Citations
“…A10). However, similar to what has been shown for the North Atlantic in coarse resolution ESM projections (Whitt, 2019;Tagklis et al, 2020;Whitt and Jansen, 2020), the decrease in nutrient supply is also controlled by the sub-surface nutrient reservoir and the fluxes fueling it. Nitrate concentrations in the top 400 metres strongly decrease under our global-warming scenario (Fig.…”
Section: Decline In Nutrient Supply Pathwayssupporting
confidence: 72%
“…Previous coarse resolution modelling studies (Whitt, 2019;Tagklis et al, 2020;Whitt and Jansen, 2020) have suggested that the climate-change-driven decline in North Atlantic NPP is strongly linked to changes in the Meridional Overturning Circulation (MOC). This link presumes that the slowdown in the upper branch of the MOC is associated with a decrease in the strength of the portion of the Gulf Stream that conveys nutrients northward (Whitt, 2019).…”
Section: On the Role Of Circulation Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low nitrate values in the mixed layer have doubled (i.e., an increase of~0.25 µmoles kg −1 ) over the past two and a half decades while suspended particulate organic matter and dissolved organic carbon have increased by~30% and 2% per decade, respectively 33 . Other studies indicate that the nutrient stream supporting production in the subtropical North Atlantic has reduced 35 . These puzzles are not addressed here, but likely includes the loss of oxygen from the surface ocean due to gas flux, and perhaps supplies of new nitrogen sources from nitrogen fixation and dissolved organic nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have attributed these rapid regional declines in Subarctic Atlantic Ocean productivity to particularly substantial reductions in the depth of surface mixing layers and a slower Atlantic meridional overturning circulation (AMOC), which led to a vertical decoupling of the surface productivity from the essential nutrients at depth (5,6,8). Based on evidence that nutrient transport in the AMOC is important for North Atlantic Ocean productivity (6,9,10), some studies recently suggested that the slowing meridional nutrient transport in the North Atlantic Ocean nutrient stream (11)(12)(13)(14)(15) (which occurs in conjunction with a slower AMOC) is a stronger physical driver of North Atlantic Ocean productivity declines in 21st-century projections than shoaling surface mixing layers (16,17). However, the mechanisms that lead to productivity decline in ESMs can be hard to disentangle (5,6,(16)(17)(18)(19)(20), and the relative importance of the physical drivers for the projected 21st-century productivity declines in the Subarctic Atlantic Ocean is not well understood.…”
mentioning
confidence: 99%